Evaluation of cervical microleakage by Enterococcus faecalis in endodontically treated teeth sealed with composite resins (Research, Society and Development, 2020)
Evaluating the cervical sealing of composite resins FBF (Filtek bulk fill), BF (Beautifil flow), YF (Yflow SA) associated with a universal adhesive system in endodontically treated teeth. Materials and Methods: The used samples in the analysis of bacterial microleakage were autoclaved, filled within a laminar flow chambre and divided in 3 experimental groups (n =5) and (n=8) according with the restorative material: Filtek Bulk Fill Flow, Beautiful Flow e Yflow SA, positive control (n=3), negative control (n=3). The samples were inoculated with E. faecalis, every 7 days and the microleakage was daily evaluated for 60 days. The data were submitted to Fisher test and survival curve of Kaplan-Meyer, and to Long-Rank. All tests were realized through SPSS, version 23.0 (IBM SPSS Inc.), considering a significance level of 0.05. Results: 12,5% of FBF specimens presented bacterial microleakage from the 30th day, YF e BF presented the highest percentual of microleakage at 30 and 50 days respectively. BF presented highest percentual of microleakage at 50 days concluding the 60 days with 40% of viable species. The test of Log Rank did not revel a significative difference between the survival curves. Conclusion: FBF, BF and YF resins were incapable promoting a hermetical sealing of root canal system filling. Clinical significance: Promote the better sealing to avoid the paissage of bactéria, consequently establishing in endodontic long term treatment.